PENERAPAN GAME EDUKASI SPLASHLEARN UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIKA PADA SISWA KELAS V SD - Rahmadita Anggraeni Putri Maulani; Neni Nadiroti Muslihah; Eko Fajar Suryaningrat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical reasoning is an essential skill that elementary school students need to develop in order to understand mathematical concepts and solve problems effectively. However, students’ mathematical reasoning ability in fraction topics remains low. This study aimed to determine the effect of implementing the Splashlearn educational game on the mathematical reasoning ability of fifth-grade elementary school students in learning fractions. The research employed a quantitative approach using a Pre-Experimental One-Group Pretest-Posttest Design. The sample consisted of 26 students from Class V-A of SDIT Persis 99 Rancabango, selected through purposive sampling. The research instrument was a mathematical reasoning test administered before and after the treatment. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Sample t-Test , and the N-Gain test. The result indicated that the mean pretest score of 59,04 increased to 82,69 in the posttest. The Paired Sample t-Test yielded a significance value (2-tailed) of 0,000 > 0,05 , indicating a significant difference between the pretest and posttest scores. Furthermore, the N-Gain score was 0,60 (60%), which falls into the moderate category, suggesting thet the use of the Splashlearn educational game was moderately effective in improving students” mathematical reasoning ability. Therefore, the implementation of the Splahlearn educational game had a positive effect on enhancing the mathematical reasoning ability of fifth-grade elementary school students in fraction learning.